2015
DOI: 10.1371/journal.pone.0145089
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of Biobanked Serum from a Mycobacterium avium subsp paratuberculosis Bovine Infection Model Confirms the Remarkable Stability of Circulating miRNA Profiles and Defines a Bovine Serum miRNA Repertoire

Abstract: Johne’s Disease (JD) is a chronic enteritis of ruminants caused by Mycobacterium avium subspecies paratuberculosis (MAP). Current disease control strategies are hampered by the lack of sensitive and specific diagnostic modalities. Therefore, novel diagnostic and prognostic tools are needed, and circulating microRNAs (miRNAs) may hold potential in this area. The aims of this study were twofold: (i) to address the stability of miRNA in bovine sera from biobanked samples, and (ii) to assess the potential of miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…The median time in storage between blood sampling and RNA isolation was 402 days (IQR: 207‐593, n = 250) with 1091 days being the maximum storage time. This is less time in storage compared with published studies that demonstrate miRNA stability when frozen . miRNA was extracted using a miRNeasy Serum/Plasma kit (Qiagen, Venlo, Netherlands) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The median time in storage between blood sampling and RNA isolation was 402 days (IQR: 207‐593, n = 250) with 1091 days being the maximum storage time. This is less time in storage compared with published studies that demonstrate miRNA stability when frozen . miRNA was extracted using a miRNeasy Serum/Plasma kit (Qiagen, Venlo, Netherlands) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies on profiling of miRNAs during clinical and subclinical infection of MAP gave a new perspective to MAP control via miRNA techniques. These studies shown that circulating miRNAs in MAP infected animals retain their integrity under longterm suboptimal storage temperatures and are considered as potential biomarkers [164, 165] that can be exploited for devising the future paratuberculosis control strategies. Apart from miRNAs several compounds such as AS101, SD169 and niclosamide can be used to target IL-10 mediated anti-inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in MAP infected cattle have measured miRNA expression in serum 8 , whole blood 9 and ileal tissues 10 . We have previously investigated circulating miRNA expression in peripheral blood at silent and subclinical MAP infection stages but detected minimal changes that did not provide diagnostic benefit 11,12 . It may, however, be more rewarding to investigate extracellular miRNAs at a local level, with faeces providing a route to explore miRNA species and abundance in the context of the intestinal immune response.…”
Section: Extracellular Micrornas (Mirnas) Are Detectable In the Peripmentioning
confidence: 99%